“Oral health as an important milieu for social and mental health”: Perspectives of adolescents emerging from a qualitative study - Lawal, Folake Barakat; Fagbule, Omotayo Francis; Lawal, Taiwo Akeem; Oke, Gbemisola Aderemi (Frontiers in Oral Health, 2022)
Background: Recent evidence had shown that prevalence of oral diseases is still high among adolescents in many developing countries including Nigeria. It therefore, becomes pertinent to focus on appropriate oral health interventions to promote oral health among them. This necessitates investigating the perspectives of adolescents, who are major stakeholders on the importance of oral health as baseline data needed in planning of appropriate primary interventions. Aim: To explore the perspectives of adolescents about the importance of oral health. Methods: An explorative qualitative study was conducted among adolescents attending Senior Secondary School I (Grade 10) in the metropolis of Ibadan, Nigeria. Twelve focus group discussions were conducted among 120 adolescents aged 14 to 19 years. Discussions were transcribed verbatim; triangulation and organization as well as thematic analysis of data were done. Results: Some adolescents had positive perception of oral health and valued it as highly important although some had contrary views and believed oral health was not important. Oral health was described as integral to general health, associated with eating and communication, a means of survival, confidence building, and as a prelude to attract opposite gender. They perceived needs for oral health education and dental treatment. Conclusion: There were mixed perspectives on the importance of oral health among the adolescents; while some valued it as highly important, others believed it was of no significance. Those who valued oral health as important described it as a milieu for general health, human survival, social and mental health thus, requested for oral health promotion in schools.